Acidification and Nitrogen Eutrophication of Austrian Forest Soils - Robert Jandl; Stefan Smidt; Franz Mutsch; Alfred Fürst; Harald Zechmeister; Heidi Bauer; Thomas Dirnböck (Applied and Environmental Soil Science)
We evaluated the effect of acidic deposition and nitrogen on Austrian forests soils. Until thirty years ago air pollution had led to soil acidification, and concerns on the future productivity of forests were raised. Elevated rates of nitrogen deposition were believed to cause nitrate leaching and imbalanced forest nutrition. We used data from a soil monitoring network to evaluate the trends and current status of the pH and the C : N ratio of Austrian forest soils. Deposition measurements and nitrogen contents of Norway spruce needles and mosses were used to assess the nitrogen supply. The pH values of soils have increased because of decreasing proton depositions caused by reduction of emissions. The C : N ratio of Austrian forest soils is widening. Despite high nitrogen deposition rates the increase in forest stand density and productivity has increased the nitrogen demand. The Austrian Bioindicator Grid shows that forest ecosystems are still deficient in nitrogen. Soils retain nitrogen efficiently, and nitrate leaching into the groundwater is presently not a large-scale problem. The decline of soil acidity and the deposition of nitrogen together with climate change effects will further increase the productivity of the forests until a limiting factor such as water scarcity becomes effective.